Biogas desulfurization using autotrophic denitrification process - ÇALLI, BARIŞ (SPRINGER, 2016)
The aim of this study was to evaluate the performance of an autotrophic denitrification process for desulfurization of biogas produced from a chicken manure digester. A laboratory scale upflow fixed bed reactor (UFBR) was operated for 105 days and fed with sodium sulfide or H2S scrubbed from the biogas and nitrate as electron donor and acceptor, respectively. The S/N ratio (2.5 mol/mol) of the feed solution was kept constant throughout the study. When the UFBR was fed with sodium sulfide solution with an influent pH of 7.7, about 95 % sulfide and 90 % nitrate removal efficiencies were achieved. However, the inlet of the UFBR was clogged several times due to the accumulation of biologically produced elemental sulfur particles and the clogging resulted in operational problems. When the UFBR was fed with the H2S absorbed from the biogas and operated with an influent pH of 8-9, around 98 % sulfide and 97 % nitrate removal efficiencies were obtained. In this way, above 95 % of the H2S in the biogas was removed as elemental sulfur and the reactor effluent was reused as scrubbing liquid without any clogging problem.
Keywords: Clogging; Elemental sulfur; Nitrate; Scrubbing; Sulfide oxidation; HYDROGEN-SULFIDE REMOVAL; MEMBRANE-BIOFILM REACTOR; BIOTRICKLING FILTERS; SEWAGE-SLUDGE; SULFUR; NITRATE; DIGESTION; KINETICS; PERFORMANCE; BIOREACTOR